The Three Seas Initiative - Luka Juri (Dela)
The study examines the Three Seas Initiative as a geopolitical and geoeconomic platform in Central and Eastern Europe and asks whether its primary purpose is economic development or a military strategy. Using a comparative analysis of the economic and geopolitical dimensions, it concludes that while the Three Seas Initiative projects offer economic benefits, they primarily serve strategic military objectives. It emphasizes the role of Three Seas Initiative in strengthening NATO capabilities and its alignment with U.S. geopolitical priorities.